Requirements of investment in the marsh : a case study in the Marshlands of Maysan - السوداني, علي موات; عباس, احمد جاسب (Journal of Economics and Administrative Sciences, 2025)
The search aims to find out the most important requirements for the success of marshes investment and maximize the expected returns of investment was marked by a problem find aquestion for availability requirements necessary for the success of marshes investment has a research community owners decision in the province Maysan the most important conclusions to the search is that the investment great importance in support of the economy and raising the cultural and social level, there is no investment successful but only with configure the investment environment appropriate economic, social, cultural, political, and security ways. the most important recommendations are working on the provision of the investment environment appropriate for investment through the elimination of security, administrative and legal obstacles and finding infrastructure adequate and dissemination of awareness of the investment to marshes resident, promotion enough to invest marshes.